2012
DOI: 10.1021/jp308798u
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structure of Organic Molecules of Intrinsic Microporosity by Molecular Simulations and X-ray Scattering

Abstract: The design of a new class of materials, called organic molecules of intrinsic microporosity (OMIMs), incorporates awkward, concave shapes to prevent efficient packing of molecules, resulting in microporosity. This work presents predictive molecular simulations and experimental wide-angle X-ray scattering (WAXS) for a series of biphenyl-core OMIMs with varying end-group geometries. Development of the utilized simulation protocol was based on comparison of several simulation methods to WAXS patterns. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 28 publications
3
60
0
Order By: Relevance
“…63 This molecular simulation methodology has been used to generate the structures for a number of PMMs to predict and understand their pore structure. Abbott et al reported the amorphous structure of 22 organic molecules of intrinsic microporosity 64 (OMIMs) with variations of functionality at the core and periphery (end-groups). 61 The simulations identified a number of structure-property relationships that lead to greater porosity.…”
Section: Amorphous Phasementioning
confidence: 99%
See 1 more Smart Citation
“…63 This molecular simulation methodology has been used to generate the structures for a number of PMMs to predict and understand their pore structure. Abbott et al reported the amorphous structure of 22 organic molecules of intrinsic microporosity 64 (OMIMs) with variations of functionality at the core and periphery (end-groups). 61 The simulations identified a number of structure-property relationships that lead to greater porosity.…”
Section: Amorphous Phasementioning
confidence: 99%
“…Importantly, the simulations described above show good agreement to empirical data, including gas adsorption. 23,64 Accordingly, simulations can be viewed as an essential tool for atomistic understanding of the properties of amorphous materials, such as the origin of porosity, that are not easily unobtainable by experimental methods alone.…”
Section: Amorphous Phasementioning
confidence: 99%
“…13,14 As mentioned already, π-stacking is unfortunately less directional than other supramolecular motifs and therefore ideal arrangements are more difficult to achieve. [9][10][11] During our initial work on organic molecules with intrinsic microporosities, [15][16][17][18][19][20][21][22] we observed a hexagonal packing of D 3h -symmetric triptycene-based large quinoxalinophenanthrophenazines (QPPs) via an unusual strong π-π interaction of the QPP blades with those of adjacent QPP molecules. 23 This packing motif could only be broken by triptycene-end-capping.…”
Section: Introductionmentioning
confidence: 99%
“…Structural hypotheses and models 14 aside, it is essentially unknown if CMPs, CTFs, and PAFs can be best described as highly branched polymers or as extended networks, or even as small but insoluble oligomers, which might nonetheless exhibit permanent microporosity. 18 This uncertainty over structure mainly stems from the amorphous or poorly crystalline nature of the experimental samples, coupled with their total lack of solubility. However, the need to understand structure–property relationships is highlighted by the recent discovery of new porous materials, such as soluble, hyperbranched CMPs and porous dendrimers, 19 organic molecules of intrinsic microporosity, 18 and other discrete organic molecules 20−24 that can show high levels of microporosity in the amorphous, solid state.…”
Section: Introductionmentioning
confidence: 99%